SINTESIS HIDROKSIAPATIT DARI CANGKANG KEONG EMAS (Pomacea canaliculata Lamarck) MELALUI METODE HIDROTERMAL - SASMITA, DEWI (IAIN Batusangkar, 2011)
The gold seashell is known as a source of calcium in hydroxyapatite synthesis [Ca10(PO4)6(OH)2]. The metal contents of the samples were analyzed by AAS. Then the hydroxyapatite synthesis was done through a hypothermal method. The analysis by FTR indicated the uptake on the tape 1.000 ? 1.200 cm-1. XRD analysis showed a sharp peak with a high intensity on 20 = 31,79o, 27,78o, and 31,09om. The analysis by SEM-EDS indicated that hydroxyapatite had the same particle size, elliptical shape like a bar premises with molar ratio 1.77.Key words: Hydroxyapatite, hydrothermal, gold seashell